The impact of the international construction standard application capability on contractors’ competitiveness: Chinese contractors’ experience - Ma, Dingyuan; Li, Xiaodong; Cheng, Chen (Journal of Civil Engineering and Management, 2020)
The application capability of international construction standards (ICS) has become a necessary element for the success of contractors in the international market. However, there is a lack of quantitative analysis of the impact of ICS application capability on contractors’ competitiveness. This paper aims to explore the driving paths between them. The authors divided the competitiveness indicators into market performance indicators and image performance indicators and developed a standard application capability measurement scale based on five dimensions (knowledge learning, talent guarantee, technical support, relationship management and organization guarantee). Then, a structural equation model (SEM), in which project performance was regarded as a mediator variable, was established to investigate the path and intensity of ICS application capability on contractors’ competitiveness. A questionnaire was distributed to the project personnel of Chinese contractors engaged in international projects, and 174 valid questionnaires were collected. The results show that 1) relationship management and technical support have a direct driving effect on the competitiveness of contractors; 2) talent guarantees and organization guarantees affect contractors’ competitiveness through project performance. This study can remind contractors of the importance of the ICS application capability and the weakness of ICS application. Additionally, it will ultimately help contractors adjust their competitiveness strategies.